Hong Kong universities: navigating in unknown waters - Horta, H; Yat Wai Lo, W (Centre for Global Higher Education, University of Oxford, 2021)
Since mid-2019, Hong Kong society was shaken by a social movement, which divided the society of Hong Kong into two sides. The social movement results from a mix of political, economic, cultural, and social tensions that have been gradually building across the years. As intense clashes between protesters and police occurred on university campuses, people have an impression that university students played an active role in the protests. In early 2020, the COVID-19 pandemic hit the territory, later the world, affecting universities as well. How did these changes influence the stability, characteristics, enrollment, and development of universities in Hong Kong?